2020
DOI: 10.1016/j.jpedsurg.2020.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Acute appendicitis during SARS-CoV-2: A brief communication of patients and changes in clinical practice from a single institute in Pakistan

Abstract: The policies for managing pediatric surgery patients were developed by surgical and anesthesia teams collectively with consultations from our hospital's infectious diseases (ID) department, and the following principles were implemented:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 1 publication
(1 reference statement)
0
9
0
Order By: Relevance
“…A small number of recent reports suggest that such changes in the management of appendicitis are not unique to the UK but have been implemented in a number of countries. [11][12][13] Interestingly, over the course of this data collection period the proportion of cases undergoing nonoperative management decreased and the proportion of cases treated surgically having a laparoscopic procedure increased over time. We suspect this pattern is a reflection of initial guidance from professional bodies proposing non-surgical treatments be sought wherever possible and cautioning against the use of laparoscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small number of recent reports suggest that such changes in the management of appendicitis are not unique to the UK but have been implemented in a number of countries. [11][12][13] Interestingly, over the course of this data collection period the proportion of cases undergoing nonoperative management decreased and the proportion of cases treated surgically having a laparoscopic procedure increased over time. We suspect this pattern is a reflection of initial guidance from professional bodies proposing non-surgical treatments be sought wherever possible and cautioning against the use of laparoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of recent reports suggest that such changes in the management of appendicitis are not unique to the UK but have been implemented in a number of countries. 11–13 …”
Section: Discussionmentioning
confidence: 99%
“…Hence, early diagnosis and appropriate treatment of AA in pediatric patients remain crucial to avoid associated complications. 50,62 Nevertheless, there were several authors who observed no significant differences in the number of children with complicated AA compared with previous years. 34,43,44,47,55 Based on data from a large German insurance company, the first COVID-19 lockdown resulted in a reduced number of pediatric appendectomies but not in an increased number of complicated AA, indicating that the confinement measures resulted in no deterioration of medical care for children with AA.…”
Section: Duration Of Appendicitis Symptoms Before Presentation During the Global Covid-19 Pandemicmentioning
confidence: 97%
“…As a general rule, some hospitals have newly adopted conservative treatment approaches for SARS-CoV-2 positive patients presenting with AA, particularly for non-complicated forms, whereas others continued to operate on all pediatric cases with AA. 43,46,51,62 The rationale for the latter is that most children with simple AA can be discharged home from the postanesthesia care unit shortly after the operation, whereas patients treated non-operatively require at least 24 hours in the hospital for intravenous antibiotics, which represent a longer time for patients and their family members being potentially exposed to SARS-CoV-2, and therefore an unnecessary use of hospital beds and medical resources. 65 Moreover, there seemed to be no reason to abandon laparoscopic appendectomy in favor of open surgery during the pandemic as SARS-CoV-2 was not detected in peritoneal fluid, thus reducing the theoretical possibility of viral transmission from aerosolization.…”
Section: Management Of Pediatric Appendicitis During the Global Covid-19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation